(untitled) (Slavic Studies, 2024)
This article looks at the problem of the imaginary lack of the motivated/productive bases for words represented in the monuments written in the Old Slavonic language. We also discuss the importance of restoring such “missing” links, as well as describe the method of supplementary explication in combination with various methods of internal reconstruction of the language and its significance for the entire word-formation system of the Old Slavonic language. Finally, we are proposing a two type schematic designation of this system: generalized and specific.